'Good health' as a barrier and facilitator to ART initiation: a qualitative study in the era of test-and-treat in Mozambique. Issue 9 (2nd September 2019) - Magaço, Amílcar; Dovel, Kathryn; Cataldo, Fabian; Nhassengo, Pedroso; Hoffman, Risa; Nerua, Lucas; Tique, José; Saide, Mohomed; Couto, Aleny; Mbofana, Francisco; Gudo, Eduardo; Cuco, Rosa Marlene; et al.
Abstract: HIV test-and-treat programmes are being implemented throughout sub-Saharan Africa, enrolling HIV-positive clients into antiretroviral treatment (ART) immediately after diagnosis, regardless of clinical stage or CD4 count. This study conducted in Mozambique examined what influenced clients who tested HIV-positive in the context of test-and-treat to make ART initiation decisions. Eighty in-depth interviews with HIV-positive clients and nine focus group discussions with health care workers were completed across 10 health facilities. 'Good health' acted simultaneously as a barrier and facilitator; clients in good health often found a positive HIV diagnosis hard to cope with since HIV was traditionally associated with ill health. Concerns about ART side effects, fear of inadvertent HIV status disclosure and discrimination, limited privacy at health facilities and long waiting times were also barriers to initiation. In contrast, being in good health also acted as a motivator to start treatment so as to remain healthy, maintain responsibilities such as work and caring for dependents and avoid unwanted disclosure. Study findings offer an in-depth understanding of the complex dynamics between individual perceptions of 'being healthy' and its influence on ART initiation within the context of test-and-treat programme implementation.